Immunomodulatory Effects of 17β-Estradiol on Epithelial Cells during Bacterial Infections. (29th August 2018) - Medina-Estrada, Ivan; Alva-Murillo, Nayeli; López-Meza, Joel E.; Ochoa-Zarzosa, Alejandra
Abstract : The innate immune system can function under hormonal control. 17 β -Estradiol (E2) is an important sexual hormone for the reproductive cycle of mammals, and it has immunomodulatory effects on epithelial cells, which are the first line of defense against incoming bacteria. E2 regulates various pathophysiological processes, including the response to infection in epithelial cells, and its effects involve the regulation of innate immune signaling pathways, which are mediated through estrogen receptors (ERs). E2 modulates the expression of inflammatory and antimicrobial elements such as cytokines and antimicrobial peptides. The E2 effects on epithelial cells during bacterial infections are characterized by an increase in the production of antimicrobial peptides and by the diminution of the inflammatory response to abrogate proinflammatory cytokine induction by bacteria. Here, we review several novel molecular mechanisms through which E2 regulates the innate immune response of epithelial cells against bacterial infections.